Recovery of Zinc during the Pre-Treatment of a Refractory Gold-Bearing Ore - Marchevsky, Natalia Judith (2013)
Mesophilic bacteria were enriched from samples collected from acid mine drainages in La Carolina(San Luis, Argentina). Two enrichments, E1 and E2, showed suitable rates of iron or sulphur oxidation, respectively. Both enrichment cultures were characterized by FISH and they were mainly composed by Leptospirillum ferrooxidans and Acidithiobacillus ferrooxidans. Studies with both,mixed and individual enrichment cultures, showed biooxidation (measured as iron solubilisation) of a refractory gold-bearing pyrite ore from Hualilán (San Juan, Argentina). Pyrite and sphalerite were the main mineral species in the ore with 7 % w/w and 8 % w/w of iron and zinc and approximately 25 ppm of gold. Leaching experiments (2 % w/v ore, 1.8 initial pH, 180 rpm and 30°C) were carried out with the addition of different alternative energy sources (6.67 g/L sulphur powder, 1 g/L iron(II), 0.02% w/v yeast extract). Redox potential, pH, iron(II) concentration and total Fe and Zn were measured regularly. A 100% of iron leaching (after 28 days in the best experimental condition) was observed in some of the cultures. In other systems high zinc release was obtained (100% of dissolution after 28 days in the best experimental condition). Our results strongly suggest that under the correct operating conditions, biooxidation pre-treatment can be used to recover zinc as a subproduct of gold extraction from refractory ore